Disentangling the physical reality of star cluster candidates projected towards the inner disc of the Large Magellanic Cloud - Piatti, Andres Eduardo (2014)
We have used Washington photometry for 90 star cluster candidates of small angular size – typically ∼11 arcsec in radius – distributed within nine selected regions in the inner disc of the Large Magellanic Cloud (LMC) to disentangle whether they are genuine physical system, and to estimate the ages for the confirmed clusters. In order to avoid a misleading interpretation of the cluster colour–magnitude diagrams (CMDs), we applied a subtraction procedure to statistically clean them from field star contamination. Out of the 90 candidate clusters studied, 61 resulted to be genuine physical systems, whereas the remaining ones were classified as possible non-clusters since either their CMDs and/or the distribution of stars in the respective fields do not resemble those of stellar aggregates. We statistically show that ∼(13 ± 6) per cent of the catalogued clusters in the inner disc could be possible non-clusters, independently of their deprojected distances. We derived the ages for the confirmed clusters from the fit of theoretical isochrones to the cleaned cluster CMDs. The derived ages resulted to be in the age range 7.8 ≤ log(t) ≤ 9.2. Finally, we built cluster frequencies (CFs) for the different studied regions and found that there exists some spatial variation of the LMC CF throughout the inner disc. Particularly, the innermost field contains a handful of clusters older than ∼2 Gyr, while the wider spread between different CFs has taken place during the most recent 50 Myr of the galaxy lifetime